Enhancing Human Resource Competence through Soft Skills and Leadership Training for Village Officials - Tri Suparyanto; Tomi Apra Santosa; Delfi Kurnia Zebua; Yucke Desma Kartika (LPPM Akademi Teknik Adikarya, 2026)
The competence of village government personnel is a key factor in achieving effective, accountable, and public service-oriented village governance. However, various challenges persist such as limited skills in communication, leadership, teamwork, problem-solving, and decision-making which impact the quality of service provided to the community. This community service initiative aims to enhance the competence of village personnel through soft skills and leadership training, thereby strengthening the institutional capacity of the village government. The implementation employs a participatory approach comprising a training needs assessment, material development, interactive training sessions, group discussions, case studies, leadership simulations, effective communication exercises, and evaluation via pre- and post-tests alongside participatory observation. Participants consisted of village personnel holding strategic roles in governance and public service delivery. The results indicate an improved understanding among participants regarding concepts such as leadership, interpersonal communication, teamwork, conflict management, service excellence, and decision-making. Furthermore, participants demonstrated increased self-confidence and collaborative abilities, as well as a commitment to applying leadership values ​​characterized by adaptability, transparency, and a focus on serving the community.